Reconsidering the Hera-Pottery from the Samian Heraion and Its Distribution - Avramidou, Amalia (Archäologischer Anzeiger, 2017)
An examination of the vases inscribed with Hera’s name from four different sanctuaries of the goddess (Samos, Naukratis, Perachora, and Gravisca) demonstrates that only two Heraia, the ones of Samos and Naukratis, have actually yielded the characteristic pottery with red dipinti marking it as Hera’s property (hence Hera-vases). The production of this local ware is examined here with reference to major construction phases of the Samian sanctuary and an attempt is made to interpret it as the main service-ware of workers rather than as equipment for ritual dining.